"Coworking Is About Community": But What Is "Community" in Coworking?. (April 2019) - Spinuzzi, Clay; Bodrožić, Zlatko; Scaratti, Giuseppe; Ivaldi, Silvia
Coworking spaces are shared working environments in which independent knowledge workers gather. Coworking is consistently described in terms of community and collaboration—yet these terms are defined inconsistently in the coworking literature. This study reviews the literature on coworking to better examine how community relates to collaboration. To anchor a more systematic analysis of community in coworking, the authors introduce Adler and Heckscher's typology of communities; apply it to a study of six coworking spaces in the United States, Italy, and Serbia; and develop the typology to better understand coworking.